2018
DOI: 10.1007/s13197-018-3242-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of replacement of sugar with jaggery on pasting properties of wheat flour, physico-sensory and storage characteristics of muffins

Abstract: Jaggery () is a natural sweetener made by concentration of sugarcane juice, contains all minerals and vitamins present in sugarcane juice. In order to utilise jaggery in place of sugar, muffins were prepared by replacing 84% sugar with 42, 63 and 84% jaggery. Different levels of eggs namely 42, 63 and 84% were also tried for jaggery muffins. The results showed that muffins prepared with 84% each of jaggery and eggs had acceptable quality characteristics. Effect of jaggery in comparison with sugar on the pastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 22 publications
4
27
0
Order By: Relevance
“…The ash content increased by 0.35% of value added shrikhand in comparison with control due to the addition of Jaggery powder accounts for total inorganic matter in the shrikhand sample S 2 reflected in the higher value of total ash. Agreement with the finding of (Lamdande et al 2018). The results obtained showed that the fat content was 7.76% to 8.80% in control and Jaggary powder added product respectively.…”
Section: Effect Of Jaggery Powder On the Nutritional Quality Of Shriksupporting
confidence: 89%
See 1 more Smart Citation
“…The ash content increased by 0.35% of value added shrikhand in comparison with control due to the addition of Jaggery powder accounts for total inorganic matter in the shrikhand sample S 2 reflected in the higher value of total ash. Agreement with the finding of (Lamdande et al 2018). The results obtained showed that the fat content was 7.76% to 8.80% in control and Jaggary powder added product respectively.…”
Section: Effect Of Jaggery Powder On the Nutritional Quality Of Shriksupporting
confidence: 89%
“…An increase of 3.37% was observed in the value added shrikhand. It may be due to more moisture content in the Jaggery powder agreement with the finding of (Lamdande et al 2018). The percentage of total solid was within the range of 47% to 56%.…”
supporting
confidence: 84%
“…Very limited literature is available on the possibility of using jaggery for 3D printing by its viscoelastic property as it can be used to partially or fully replace sugar in 3D printing which can open a wide arena for healthy alternatives using 3D printing. It has also been shown that jaggery can be used in different bakery products in place of sugar (Lamdande et al., 2018), hence, if it is found to be printable there are a wide range of products that can be printed as many products being printed now commercially, are sugar based.…”
Section: Introductionmentioning
confidence: 99%
“…The results of Lamdande, et al (2018) for evaluation of physicochemical characteristics of both the muffins showed that the moisture content of muffins prepared with jaggery was higher (21.8%) than muffins prepared with sugar (19.6%) due to presence of invert sugar, mineral salts which are hygroscopic in nature and also higher moisture content present in the jaggery (Mandal et al 2006). The protein and fat contents were slightly lower (6.38 and 30.93%) in muffins with jaggery than muffins with sugar (6.58 and 33.33%).…”
Section: -Nutritional Properties and Sensory Evaluation Of Cake Madementioning
confidence: 99%
“…As shown in Table (1), Panela or Jaggery (Gur) is a natural sweetener made by the concentration of sugarcane juice, contains all minerals and vitamins present in sugarcane juice, and therefore, it is expected that its nutritional value is higher than that of refined sugar (Kumar andTiwari, 2006 andLamdande, et al, 2018). It has been shown that panela has medicinal properties, for example, preventing lung lesions induced by smoke, due to its antioxygenic and anticarcinogenic properties (Sahu and Paul, 1998;Sahu and Saxena, 1994).…”
Section: Introductionmentioning
confidence: 99%